Nosocomial Parasitic Infections - Sankur, Funda (European Journal of Therapeutics, 2023)
Nosocomial infections develop a minimum of 48 h after hospital admission in patients who are free from infections at the time of admission. In addition to other agents that cause infection, the etiology of nosocomial infections involves various parasites. In light of literature data, the aim of this review was to address the agents that cause nosocomial parasitic infection.